Isolation and characterization of Lactobacillus strains as potential probiotics for chickens - Shokryazdan, Parisa; Ramasamy, Kalavathy; Sieo, Chin Chin; Mohamed Alitheen, Noorjahan Banu; Liang, Juan Boo; Jahromi, Mohammad Faseleh; Ho, Yin Wan (Universiti Putra Malaysia Press, 2014)
The ban on the use of antibiotics as growth promoters for poultry production in many countries has led to increasing interest to use probiotics as an alternative. In the present study, some Lactobacillus strains were isolated from chicken intestines, identified and assessed (in vitro) for their ability to survive and colonize the gastrointestinal tract (GIT), with a view to select suitable strains as potential probiotic candidates for chickens. Out of 42 isolated strains, three isolates, identified as Lactobacillus strains based on initial identification and tolerant to acid and bile based on preliminary screening using turbidity (optical density) as a measurement of growth, were selected for detailed identification and further in vitro assays. The three isolates were identified to species level using carbohydrate fermentation profile analysis and 16S rRNA gene sequencing. Results showed that all three strains belonged to Lactobacillus salivarius. The three L. salivarius strains were then assessed for their ability to tolerate the stress conditions in the GIT and capacity to adhere to the intestinal epithelial cells using in vitro assays of acid, bile and pancreatic enzyme tolerance measured by viable colony counts, and adhesion assay using Caco-2 cell line. The results showed that all three L. salivarius strains exhibited good tolerance to acid, bile and pancreatic enzymes and a strong ability to adhere to intestinal epithelial cells. Thus, they would be able to survive the stress conditions of GIT, as well as to attach and colonize the GIT, and could be considered as good potential candidates for probiotics of chickens.